Business plan Sweet Love Bakery / Ahmad Azlan Azizan... [et al.] - Azizan, Ahmad Azlan; Kamalaudin, Puteri Nordina; Hamzah, Hafizah (2007)
A bakery is a place where production of breads takes place. Sweet Love Bakery aims to be the main producer and supplier of baked goods in Samarahan and the surrounding area. In order for this to have effect, high co operation is needed between the gears of Sweet Love Bakery itself. In today's world, customers want the best out of their daily intake of foods. We found that bread is in the top tier of the universal food chain. Bread is also one of the most needed foods for daily consumption of one healthy adult. If we take a time to browse the products sold in bookstores and stalls alike, we are most likely to see an article featuring recipes on how to make baked goods. Considering the fact that people are exposed to this all the time, Sweet Love Bakery is willing to take the risk by venturing into the business of producing baked goods for the customers. Furthermore, customers are getting smarter and picky about their daily intake of food. We are willing to satisfy that needs and produce specially selected products for their everyday needs by producing first-rate dough-related products. There are criteria and conditions that have to be fulfilled which require the involvement of effort and precision of producing baked goods. Without such conditions, the business cannot run properly and organizational goals will not be achieved. These conditions must be achieved in order for the business to take position in the first place.